Cu-doping of calcium phosphate bioceramics: From mechanism to the control of cytotoxicity. (January 2018) - Gomes, Sandrine; Vichery, Charlotte; Descamps, Stéphane; Martinez, Hervé; Kaur, Amandeep; Jacobs, Aurélie; Nedelec, Jean-Marie; Renaudin, Guillaume
Graphical abstract: Abstract: In this study, the Cu-doping mechanism of Biphasic Calcium Phosphate (BCP) was thoroughly investigated, as was its ionic release behavior, in order to elucidate cytotoxicity features of these bioceramics. BCP are composed of hydroxyapatite (Ca10 (PO4 )6 (OH)2 ) and β -TCP (Ca3 (PO4 )2 ). The two phases present two different doping mechanisms. Incorporation into the β -TCP structure is achieved at around 700 °C thanks to a substitution mechanism leading to the Cu-doped Ca3− x Cu x (PO4 )2 compound. Incorporation into the HAp structure is achieved thanks to an interstitial mechanism that is limited to a Cu-poor HAp phase for temperatures below 1100 °C (Ca10 Cu x (PO4 )6 (OH)2−2 x O2 x with x  < 0.1). Above 1100 °C, the same interstitial mechanism leads to the formation of a Cu-rich HAp mixed-valence phase (Ca10 Cu 2+ x Cu + y (PO4 )6 (OH)2−2 x-y O2 x+y with x  +  y  ∼ 0.5). The formation of both high-temperature Cu-doped α-TCP and Cu3 (PO4 )2 phases above 1100 °C induces a transformation into the Cu-rich HAp phase on cooling. The linear OCuO oxocuprate entity was confirmed by EXAFS spectroscopy, and the mixed Cu + /Cu 2+ valence was evidenced by XPS analyses. Ionic releases (Cu + /Cu 2+, Ca 2+, PO4 2− and OH − ) in water and in simulated body media were investigated on as-synthesized ceramics to establish a pretreatment before biological applications. Finally the cytotoxicity of pretreated disks was evaluated, and results confirm that Cu-doped BCP samples are promising bioceramics for bone substitutes and/or prosthesis coatings. Statement of Significance: Biphasic Calcium Phosphates (BCP) are bioceramics composed of hydroxyapatite (HAp, Ca10 (PO4 )6 (OH)2 ) and beta-Tricalium Phosphate ( β -TCP, Ca3 (PO4 )2 ). Because their chemical and mineral composition closely resembles that of the mineral component of bone, they are potentially interesting candidates for bone repair surgery. Doping can advantageously be used to improve their biological behaviors; however, it is important to describe the doping mechanism of BCP thoroughly in order to fully appraise the benefit of the doping process. The present paper scrutinizes in detail the incorporation of copper cation in order to correctly interpret the behavior of the Cu-doped bioceramic in biological fluid. The understanding of the copper doping mechanism, related to doping mechanism of others 3d-metal cations, makes it possible to explain the rates and kinetic of release of the dopant in biological medium. Finally, the knowledge of the behavior of the copper doped ceramic in biological environment allowed the tuning of its cytotoxicity properties. The present study resulted on pre-treated ceramic disks which have been evaluated as promising biocompatible ceramic for bone substitute and/or prosthesis coating: good adherence of bone marrow cells with good cell viability.